Applications of distress prediction models: What have we learned after 50 years from the Z-Score models? - Edward I. Altman (International Journal of Financial Studies, 2018)
Fifty years ago, I published the initial, classic version of the Z-score bankruptcy prediction models. This multivariate statistical model has remained perhaps the most well-known, and more importantly, most used technique for providing an early warning signal of firm financial distress by academics and practitioners on a global basis. It also has been used by scholars as a benchmark of credit risk measurement in countless empirical studies. Practical applications of the Altman Z-score model have also been numerous and can be divided into two main categories: (1) from an external analytical standpoint, and (2) from an internal to the distressed firm viewpoint. This paper discusses a number of applications from the former's standpoint and in doing so, we hope, also provides a roadmap for extensions beyond those already identified.
Keywords: 330; Altman Z-score; bankruptcy prediction; fixed income investments; equity investments; ratings; regulators; auditors